A new chart of hydraulic fracture height prediction based on fluid–solid coupling equations and rock fracture mechanics. Issue 10 (10th October 2018) - Liu, Xiaoqiang; Qu, Zhanqing; Guo, Tiankui; Wang, Dongying; Tian, Qizhong; Lv, Wei
Abstract : The conventional method to predict hydraulic fracture height depends on linear elastic mechanics, and the typical Gulrajani–Nolte chart fails to reflect fracture height when the net pressure in the fracture is too high. Based on fluid–solid coupling equations and rock fracture mechanics, a new chart is obtained by the ABAQUS extended finite-element method. Compared with the Gulrajani–Nolte chart, this new chart shows that longitudinal propagation of hydraulic fracture is still finite when the net pressure in the fracture is higher than in situ stress difference between reservoir and restraining barrier. The barrier has a significant shielding effect on the longitudinal propagation of hydraulic fracture, and there is a threshold for an injection rate of fracturing fluid to ensure hydraulic fracture propagates in the barrier. Fracture height decreases with the increase of in situ stress difference. When the ratio of net pressure to in situ stress difference is less than 0.56, the propagation of hydraulic fracture is completely restricted in the reservoir. Hydraulic fracturing parameters in Well Shen52 and Well Shen55 are optimized by using the new chart. Array acoustic wave logging shows that the actual fracture height is at an average error within 14.3% of the theoretical value, which proves the accuracy of the new chart for field application.